Strategi Pelayanan dalam Rangka Meningkatkan Kunjungan Wisata ke Pantai Busung (Studi Kasus Pada Kantor Dinas Pariwisata dan Kebudayaan kabupaten Simeulue) - Anggi Funga Nauli; Indra Muda; Armansyah Matondang (Universitas Medan Area, 2022)
attraction is able to increase the community’s economy and create jobs. The Problem in this reseach is how to the service in order to increase the tourist visits of Busung Beach and the obstacles that influence it. Method used was descriptive with a qualitative approach, namely describing data from the field and then explaining it the words. The data collection technique is triangulation in three ways, namely observation, interviews, documentation. This study involvet 7 informant, namely 2 key informants, 2 main informants, 3 additional informants. There are four factors that become the basis for analyzing the Busung Beach tourism servicy strategy, namely strangth, weaknesses, opportunities and threats. From this analysis, there are obstacles that affect tourist visit, namely the lack of community participation, the number of other tours that are competitors, the lack of creativity from the community, the lack of connecktivity, the limited skilled workforce. Based on the results of the study, it can be concluded that the strategy carried out by Busung Beach tourism objecks is to involve the community to maintain the beauty of the beach so that it looks well- geoomed and does not affect the natural exoticism of the beach, provide adequate supporting faciities (prayer rooms, toilets, tourist huts, beachside cafes, boats), showing the hospotality of thr coast guart to tourist visitors, providing a fairly large play area, easy accessability to the beach, which is guaranteed enough security to increase Busung Beach tourism visitors.